A Three-Dimensional Contextualization Established for an English Language-Learning-&-Teaching to Get Along With in the Classroom - Yan Pei-heng; Yan Jing; Chen Si (International Conference on Education and Language (ICEL), 2014)
If language is supposed to be the text, the question then comes towhat is the context within which language lives rather than die? What context to language-learningis  what water to plant-surviving. Questionably, what is thought of previously as the context or linguistic environment, especially that for classroom situation, remains still a problem to be dealt with and, what this paper is trying to do is therefore to establish kind of three-dimensionalcontextualization, which is hypothesized as being verbal and non-verbal, cultural and non-cultural as well as linguistic and non-linguistic for language teaching-and-learning to be carried out inside the classroom and, if possible, for English teachers to get along with.